Weight Gain During Adulthood and Body Weight at Age 20 Are Associated With the Risk of Endometrial Cancer in Japanese Women - Hosono, Satoyo (Japan Epidemiological Association, 2011)
BACKGROUND: Current obesity is an established risk factor for endometrial cancer; however, the roles of weight gain during adulthood and obesity in early adulthood on endometrial cancer have not been elucidated. Here, we conducted a case-control study comprising 222 histologically diagnosed incident endometrial cancer cases and 2162 age- and menstrual-status matched non-cancer controls. METHODS: Information on current body weight, weight and height at age 20 years, and lifestyle/environmental factors was obtained from a self-administered questionnaire. Subjects were classified into 3 groups according to change in body mass index (BMI, kg/m(2)) from age 20 years to enrollment (≤0 [reference], 0–3, and >3 kg/m(2)). The effects of adult BMI change and obesity in early adulthood were evaluated using an unconditional logistic regression model adjusted for potential confounders. RESULTS: A high BMI at age 20 (BMI ≥25, BMI <25 as reference) was significantly positively associated with endometrial cancer risk (P = 0.005), as was a BMI increase during adulthood (0–3 BMI change, multivariate odds ratio [OR] = 1.28, 95% confidence interval [CI] = 0.88–1.87; >3 BMI change, OR = 2.02, 95% CI = 1.38–2.96; P-trend < 0.001). Parity and BMI at age 20 appeared to modify the effect of weight gain on cancer risk, albeit without statistical significance. This positive association of weight gain with risk was observed only for endometrioid adenocarcinoma. CONCLUSIONS: The results show that endometrial cancer is positively associated with obesity at age 20 and weight gain during adulthood among Japanese women.